A Charlie Brown Christmas [videorecording (DVD)] - Schulz, Charles M. (Charles Monroe), 1922-2000; Melendez, Bill (Peanuts classic., 2000)
'Tis the season to be jolly, but Charlie Brown, feeling that the Christmas message is lost amid all the seasonal glitter, has the blues. Join the Peanuts gang as they discover for themselves the true meaning of Christmas.